2020
DOI: 10.3390/ijms21030853
|View full text |Cite
|
Sign up to set email alerts
|

Lung Macrophage Functional Properties in Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is caused by the chronic exposure of the lungs to toxic particles and gases. These exposures initiate a persistent innate and adaptive immune inflammatory response in the airways and lung tissues. Lung macrophages (LMs) are key innate immune effector cells that identify, engulf, and destroy pathogens and process inhaled particles, including cigarette smoke and particulate matter (PM), the main environmental triggers for COPD. The number of LMs in lung tissues and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 207 publications
(272 reference statements)
2
39
0
3
Order By: Relevance
“…We also showed that the proportion of these non-polarized macrophages increases with increasing COPD severity, suggesting that these macrophages could contribute to the progression of disease, though additional studies will be required to establish causality. Previous studies have shown that lung macrophages in COPD have reduced phagocytic ability [ 17 , 21 , 22 ], and here we showed that these non-polarized macrophages predominantly contribute to this impaired phagocytic activity. This reduced phagocytic activity of non-polarized macrophages was also related to the severity of the underlying COPD.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…We also showed that the proportion of these non-polarized macrophages increases with increasing COPD severity, suggesting that these macrophages could contribute to the progression of disease, though additional studies will be required to establish causality. Previous studies have shown that lung macrophages in COPD have reduced phagocytic ability [ 17 , 21 , 22 ], and here we showed that these non-polarized macrophages predominantly contribute to this impaired phagocytic activity. This reduced phagocytic activity of non-polarized macrophages was also related to the severity of the underlying COPD.…”
Section: Discussionsupporting
confidence: 75%
“…The clinical relevance of this observation, however, is unclear, although this phenotypic shift of macrophages in COPD supports the notion that these non-polarized macrophages contribute to the persistent inflammatory responses in lung tissues of COPD [ 6 , 7 ]. A few studies have previously addressed the issue of macrophage phenotypes shifts in COPD [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. Kunz and coworkers, for example, used induced sputum samples (which represents mostly macrophages from the larger airways) to evaluate M1 and M2 phenotypes [ 15 ], while Eapen and co-workers [ 12 ], using macrophages harvested from BAL fluids, evaluated different phenotypes of macrophages and found that the percentage of non-polarized macrophage increased in COPD subjects; results that were similar to the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations